On-Site Identification of Pottery with pXRF: An Example of European and Chinese Red Stonewares - Gulsu Simsek Franci; Philippe Colomban (Heritage, 2021)
The invention of European hard porcelain, which aims at imitating kaolin-containing white paste of Chinese porcelain, had been started by the development of the technology of “red porcelain”, so-called “Jaspisporzellan” by Johann Friedrich Böttger in the early-eighteenth century at Meissen (Saxony). The visual features of the earlier Böttger red stoneware were rather similar to the one produced in Yixing, China. The prominence of Böttger productions allowed the manufacturing to be expanded across Europe to different countries (Holland, England, France, etc.). In this study, the chemical characteristics of nine European unglazed objects produced in England, France, Russia, and Holland from the 17th to 19th century and 10 Chinese (unglazed or enameled) red stoneware have been studied by using an on-site characterization technique pXRF. The results were compared with the previous studies carried out on 25 unglazed, polished, and non-polished Böttger artefacts. This non-invasive, speedy technique allows a methodology to be created for distinguishing the technological differences related to the provenance and authenticity of the artefacts. The elemental measurements explicitly show the significant discrepancy of Dutch objects from the main group, which involves other European and Chinese ones. Both a Lambertus van Eenhoorn (Delft) statue and an Ary de Milde (Delft) teapot are distinguishable from other European red stoneware by the high content of iron and calcium and high content of titanium and potassium, respectively, found in their body compositions. An overall comparison was made between the measurements made at different times in order to evaluate the error range arising from the measurement procedure (e.g., energy resolution of other series of the same instrument model).